Effect of Nutrient on the Bio-Ethanol Production from Pineapple Peel Fermentation - Harita N Chamidy; Saripudin; Ayu Ratna Permanasari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Addressing the problem of increasingly complex urban household waste requires a multi-aspect approach. Bioethanol fermentation from pineapple peel juice is interesting research to carry out because pineapple peel is one of the fruit wastes that has the potential to be used as raw material for bioethanol production. Disposal of pineapple peel waste can causeenvironmental problems because this waste can become a source of water and air pollution if not managed properly. Therefore, processing pineapple peel waste into useful products such as bioethanol can help reduce the environmental impact of waste disposal. This research discusses the effect of nutrient concentration on bioethanol production in the fermentation process from pineapple peel. The nutrients used include urea and NPK (Nitrogen, Phosphorus, Potassium) which are added during fermentation with varying nutrient concentrations of 11.25 g, 22.50 g,and 33.75 g. This research also considered the initial fermentation conditions, namely the sugar contentof pineapple peel juice of around 4 Brix and a pH in the range of 5.5 to 6.0. Fermentation results are measured in the form of bioethanol content, with production targets of 6%, 7.5% and 9%. Higher nutrient concentrations tend to support better yeast growth and higher ethanol production. However, it should be noted that a proper balance between nutrient concentrations needs to be achieved to avoid negative impacts such as overstimulation and the production of undesirable compounds.